2017
DOI: 10.1680/jgeot.15.p.046
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction perspective of soil ageing

Abstract: Subsoil liquefaction during strong earthquakes is one of the major seismic threats to the human community. Over the past few decades various methodologies have been proposed to assess liquefaction vulnerability; however, recent seismic events in Japan have revealed that current assessment methods are over conservative, which results in unnecessarily higher costs in mitigation measures. To overcome this situation, this study reinterprets the dynamic behaviour of sandy subsoils subject to recent and historical g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(1 citation statement)
references
References 31 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…Teparaksa and Koseki (2018) [33], by application of cyclic history in loose sand and in dense sand, reported that liquefaction resistance depends on densification processes. Towhata et al (2017) [34], using field investigation results, demonstrated the existence of aging of liquefaction resistance in actual ground, including effects of the cyclic history.…”
Section: Introductionmentioning
confidence: 97%
“…Teparaksa and Koseki (2018) [33], by application of cyclic history in loose sand and in dense sand, reported that liquefaction resistance depends on densification processes. Towhata et al (2017) [34], using field investigation results, demonstrated the existence of aging of liquefaction resistance in actual ground, including effects of the cyclic history.…”
Section: Introductionmentioning
confidence: 97%